Celastrol protects ischaemic myocardium through a heat shock response with up‐regulation of haeme oxygenase‐1. (December 2014) - Der Sarkissian, S; Cailhier, J‐F; Borie, M; Stevens, L‐M; Gaboury, L; Mansour, S; Hamet, P; Noiseux, N
<x xml:space="preserve">Abstract</x> Background and Purpose Celastrol, a triterpene from plants, has been used in traditional oriental medicine to treat various diseases. Here, we investigated the cardioprotective effects of celastrol against ischaemia. Experimental Approach Protective pathways induced by celastrol were investigated in hypoxic cultures of H9c2 rat cardiomyoblasts and in a rat model of myocardial infarction, assessed with echocardiographic and histological analysis. Key Results In H9c2 cells, celastrol triggered reactive oxygen species (ROS) formation within minutes, induced nuclear translocation of the transcription factor heat shock factor 1 (HSF1) resulting in a heat shock response (HSR) leading to increased expression of heat shock proteins (HSPs). ROS scavenger N‐acetylcysteine reduced expression of HSP70 and HSP32 (haeme oxygenase‐1, HO‐1). Celastrol improved H9c2 survival under hypoxic stress, and functional analysis revealed HSF1 and HO‐1 as key effectors of the HSR, induced by celastrol, in promoting cytoprotection. In the rat ischaemic myocardium, celastrol treatment improved cardiac function and reduced adverse left ventricular remodelling at 14 days. Celastrol triggered expression of cardioprotective HO‐1 and inhibited fibrosis and infarct size. In the peri‐infarct area, celastrol reduced myofibroblast and macrophage infiltration, while attenuating up‐regulation of TGF‐β and collagen genes. Conclusions and Implications Celastrol treatment induced an HSR through activation of HSF1 with up‐regulation of HO‐1 as the key effector, promoting cardiomyocyte survival, reduction of injury and adverse remodelling with preservation of cardiac function. Celastrol may represent a novel potent pharmacological cardioprotective agent mimicking ischaemic conditioning that could have a valuable impact in the treatment of myocardial infarction.